The Role of Local Aggregator in Delivering Energy Savings to Household Consumers - Leila Luttenberger Marić; Hrvoje Keko; Marko Delimar (Energies, 2022)
Energy communities, also known as renewable or citizen energy communities, can be a source of innovative aggregation solutions at the local level. The unleashed flexibility potential of households could provide self-balancing services for local energy communities or create new revenue streams for local flexibility aggregators. This paper proposes a methodology for the assessment of the energy savings potential of residential customers, factoring in local climatological conditions, energy consumption patterns, and building energy performance when the available input data are scarce. For baseline consumption modelling, the correlation between historical energy consumption data collected from a survey, building energy performance parameters, and the availability of flexibility assets was determined, taking into account the inconsistency between the quantity and quality of collected data from various consumers. For this purpose, a modelling approach using calculations for “Agent” buildings was used. In this way, each building user was assigned to a specific “Agent” with dedicated consumption characteristics for a flexibility asset. The capacities engaged in a flexibility programme were modelled according to the available flexibility assets, whilst the duration of a flexibility demand response (DR) event was considered a function of building energy performance characteristics, and consequently, activation strategies were applied. Additionally, several energy savings activation scenarios were modelled to interlink technical and behavioural constraints of household consumers. These constraints restrict the available flexibility, thus influencing the possibility of daily repetitions of a DR event and increasing savings with flexibility event activation. This model is intended to optimise flexibility assets provided by the end-users and, in this manner, deliver permanent energy savings, offering new business opportunities for aggregators or local energy communities. The novelty of this research is the recognition of an aggregator as a permanent energy savings provider, even if the obtained savings are very conservative per individual flexibility asset. Nevertheless, if properly aggregated and identified, the obtained savings could create novel business opportunities for a local aggregator.